2010
DOI: 10.1007/s10570-010-9444-4
|View full text |Cite
|
Sign up to set email alerts
|

Inverse gas chromatography analysis of spruce fibers with different lignin content

Abstract: Unbleached TMP spruce fibers were stepwise delignified by KMnO 4 /H 2 SO 4 and five partly delignified samples were obtained. Fibers were characterized in terms of carboxylic groups, lignin and hemicelluloses content. IGC measurements were performed in the untreated fibers and in the five delignified fiber samples, as well as in microcrystalline cellulose (MCC). Different parameters, such as the dispersive component of the surface free energy (c a of the acidic probes decrease with the delignification whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Another issue related to changes in surface properties is the migration of extractives to the surface (Kazaywoko et al 1997;Nuopponen et al 2003;Sernek et al 2004;Källbom et al 2015). Other studies of UW components from spruce showed similar results to this study; 42 mJ/m 2 (Wålinder and Gardner 2000;Peterlin et al 2010) and 41 mJ/m 2 (Cordeiro et al 2012). In previous studies of the surface energy of TMW from spruce determined by contact angle measurement, the dispersive part of the surface energy was increased, whereas the polar part was decreased with thermal modification temperature (Kutnar et al 2013;Altgen et al 2016a).…”
Section: Surface Propertiessupporting
confidence: 84%
See 1 more Smart Citation
“…Another issue related to changes in surface properties is the migration of extractives to the surface (Kazaywoko et al 1997;Nuopponen et al 2003;Sernek et al 2004;Källbom et al 2015). Other studies of UW components from spruce showed similar results to this study; 42 mJ/m 2 (Wålinder and Gardner 2000;Peterlin et al 2010) and 41 mJ/m 2 (Cordeiro et al 2012). In previous studies of the surface energy of TMW from spruce determined by contact angle measurement, the dispersive part of the surface energy was increased, whereas the polar part was decreased with thermal modification temperature (Kutnar et al 2013;Altgen et al 2016a).…”
Section: Surface Propertiessupporting
confidence: 84%
“…The surface energy properties are related to the surface chemical composition, eg functional groups or extractives present at the surface (Tshabalala 1997). Several studies have applied the IGC technique to study the surface energy properties of milled wood components, ie wood flour (Kamdem et al 1993;Tshabalala 1997;Liu et al 1998;Gardner 2000, 2002;Peterlin et al 2010;Cordeiro et al 2012). The results from these studies provide single values of the surface energy, representing the highest energy sites of the surface based on very low solute concentration.…”
Section: Introductionmentioning
confidence: 99%